Reliable Encryption Algorithm Used For Communication - Kakkar, Ajay (My University, 2007)
In today’s worlds security is an important part of our life. It will be achieved by various techniques such as passwords, cryptography, biometrics and more techniques. In this work cryptography is discussed with its parameters. The work discusses what is cryptography and why it is needed. It is an ancient art that passed through many paradigms, from simple letter substitutions to poly-alphabetic substitutions to digital encryption to public-key cryptosystems. Cryptography has been used since the dawn of writing itself to conceal message from an adversary. Throughout history, the use of cryptography has been largely confined to diplomatic and military communications. It is method of saving or protecting our data/information from the hacker. Passwords are not so good for this because they are often easy to guess by automated programs. In this thesis there is a technique derived from Polybius. The main of cryptography export laws is to prevent potential adversaries from gaining accesses to encryption technologies that might reveal important characteristics of information security products. In cryptography we cannot achieve 100% security. The encrypted data is safe for sometime but never thought it is permanently safe, as the time goes on there is chance of hacking the data by the hacker. So to avoid this we make the system more complex by using Data encryption Standard (DES), which is very hard to break. As we go on increasing security by means of increasing the key bit length, this will also increase the overheads. The efficient cryptography must have minimum number of overheads and have simple encryption algorithm. An efficient algorithm has been developed in this work, which is used for encrypting the data with two keys by keeping an eye on the key bit length.
Keywords: Reliable Encryption Algorithm; Communication